Fenomena al-Qur’an: Tafsir Integral Malik Bennabi - Usman Syihab Husnan (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2004)
This article delves into the pattern of interpretation or approach taken by Malik Bennabi in understanding the Qur'an. Malik Bennabi's approach to revelation is integral in nature. By examining Malik's work,